Using digital reading platforms to enhance motivation in english reading - Kupaysinova, Zarifa (The Lingua Spectrum, 2026)
This study is devoted to investigating the effectiveness of digital reading platforms in developing high school students’ reading motivation and reading comprehension skills in English language classes. The research was conducted with 64 Grade 10 students of a secondary school. The experimental group used a digital reading platform for eight weeks, while the control group received instruction based on traditional printed learning materials. Data were collected through questionnaires, reading comprehension tests, platform usage records, and interviews. The results showed that reading motivation and reading comprehension indicators improved significantly more in the experimental group than in the control group. This confirms that the purposeful use of digital reading platforms under teacher guidance can effectively develop students’ reading skills.